L’analyse collective des accidents du travail - Claudia Osorio; Yves Clot (Activités)
The ACAT system (group analysis of industrial accidents), adopted as an intervention research method for hospital workers’ health, has been developed since 2002 in a public hospital in the city of Rio de Janeiro. It aims at, on the one hand, analysing accidents by taking into account the realities of the work, and on the other hand, increasing the vitality of occupational constructs (Clot, 2008) in the hospital environment. The twin goals of this intervention research are to generate new knowledge about work in hospitals and to increase the involvement of doctors, nurses and other health professionals in managing their daily routines.The method consists of asking a worker to recreate the scene of an accident by imagining himselves as an observer. First of all, he are asked to describe how the accident happened through an account of the movements and actions that led up to it. The researcher asks questions about the choices made about the various technical ways the actions might have been performed, what interruptions occurred and other details. The worker and researcher then record the sequence of events described in the form of a diagram, putting the emphasis on the worker’s experience. Next, group discussions are held about several accidents, always with the objective of increasing workers’ awareness of their own actions.The methodology aims to contribute to a psychology of work that would be instrumental in encouraging individuals to reduce risk, through the development of occupational constructs. With this in mind, it uses a combination of the concepts of workers’ health surveillance developed in Brazil, and French institutional and clinical work analysis.The results obtained so far show that the method does indeed help workers to put themselves in the position of observers and co-analysts of their own work. It has also led to new understanding and new ways of performing tasks by breaking down entrenched habits that hinder the development of occupational constructs in the hospital environment.